Duhamel, Jérémie (2016). Les Vertus de la liberté. Machiavel et la critique de la domination. Paris, Francia: Classiques Garnier. 198 pp. - Vernazza, Diego (Las Torres de Lucca. International Journal of Political Philosophy, 2017)
The blows of history seem, in recent times, to harden. Or it is perhaps the insistent way they have to pile up, one after another, which makes them more acute. Meanwhile, there are breaths, and questions. On how to act politically in this context, on how to sustain the commitment to democratic equality in a world that faces chaos between restoration and conformism.I thought of that and more after reading the book of Jérémie Duhamel, Les vertus de la liberté. Machiavel et la critique de la domination, recently published in Paris, in Classiques Garnier.